RISKS OF TOMATO FARMING DURING THE RAINY SEASON IN AIMOLI VILLAGE, WEST ALOR DISTRICT - Elvani, Siska; Bureni, Eman Nevianus; Taloim, Aristarkhus (Undana Press, 2025)
The objectives of this study were to determine 1) the risks of tomato farming during the rainy season in Aimoli Village, Alor Barat Laut District, 2) the comparison of tomato production during the rainy season in Aimoli Village, Alor Barat Laut District, and 3) the comparison of tomato income during the rainy season in Aimoli Village, Alor Barat Laut District. The research was conducted in September 2024 with a sample size of 58 tomato farmers. The results showed that: 1) The risks faced by tomato farmers in Aimoli Village were income risk, revenue risk, and production risk. The amount of income and revenue earned by tomato farmers in the dry season and rainy season differs due to differences in selling prices and production volumes. 2) In the dry season, tomato production in Aimoli Village reached 107 kg, while tomato production in the rainy season reached 45 kg. 3) The difference in tomato production between the dry season and rainy season causes a difference in the income levels of tomato farmers in Aimoli Village.